The reasons for the decline of American hegemony and its impact on China's regional policies in the Middle East - Aghili Dehnavi, Ellias (2020)
The present study examines the causes of the decline of American hegemony and its impact on China's regional policies in the Middle East. Discussion of the decline of American hegemony is one of the materials on which there are different views. This issue is of great importance because of its impact on international politics. The reasons for the declining US hegemony trend and its impact on China's regional policies in the Middle East have not been addressed yet. The key question that has been addressed in this regard is what are the reasons for the decline of American hegemony and its impact on China's regional policies in the Middle East? The present study is a descriptive-analytic one and uses library method to investigate the mentioned question. The results indicate that the trend toward US hegemony is declining, citing the need for multilateralism, the US financial crisis, and its impact on the country's financial and manufacturing industry and the emergence of new powers, including China. The declining trend of American hegemony has influenced China's regional policy. The decline in US influence has provided China with an opportunity to trade and energy. China's strong need for energy resources in the Middle East has made it present more actively than ever in the Middle East as it has concluded numerous oil contracts with Saudi Arabia, Iraq and Iran.